Information and the Transformation of Sociology: Interactivity and Social Media Monitoring - Hugh Mackay (tripleC: Communication, Capitalism & Critique)
This paper explores some key ways in which the scale and form of information today challenges sociology’s methods and practice. Information has shaped sociology in two key ways. First, it has become an object of study, largely in the form of accounts of ‘the information society’. This paper argues that interactivity is a key element of such changes, albeit a notion has not been a major focus of information society theorists. The second way in which sociology is being transformed by the growth of information is that, with the growth of huge volumes of commercial transactional information, social information is no longer the preserve of sociologists. Moreover, new tools have emerged to challenge the research methods that lie at the heart of sociology. Linking the growth of interactivity with new forms of data and research tools, this paper discusses the case of the BBC World Service’s use of social media monitoring tools. The paper concludes by arguing that the vast amount of available information affords new possibilities for sociologists as well as for the organisations that collect it.